Synthesis and microwave absorption properties of graphene-oxide(GO)/polyaniline nanocomposite with gold nanoparticles*Project supported by the National Basic Research Program of China (Grant Nos. 2011CB932700 and 2011CB932703), the National Natural Science Foundation of China (Grant Nos. 61335006, 61378073, and 61077044), and the Beijing Natural Science Fund (Grant No. 4132031). (August 2015) - Fu, Chen; Da-Wei, He; Wang, Yong-Sheng; Fu, Ming; Geng, Xin; Zhuo, Zu-Liang
Abstract A composite of graphene/PANI/GAunano is synthesized using the co-blend method. The morphologies and microstructures of samples are examined by transition electron microscopy (TEM) and Fourier transform infrared spectroscopy (FTIR). Moreover, the microwave absorption properties of both graphene/PANI and GO/PANI/ GAunano composites are investigated in a microwave frequency band from 1 GHz to 18 GHz. The maximum reflection loss (RL) of GO/PANI/GAunano with a thickness of 2 mm is up to −24.61 dB at 15.45 GHz, and the bandwidth corresponding to RL at −10 dB can reach 4.08 GHz (from 13.92 GHz to 18.00 GHz) for a 2-mm-thick layer. The electromagnetic data demonstrate that GO/PANI/GAunano can be used as an attractive candidate for microwave absorbers.